Pengaruh Pendidikan dan Pelatihan Terhadap Produktivitas Karyawan - lubis, kartika sari (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Abstract: The purpose of this research was to determine the effect of Education and Trainingon work Productivity of employees Production. Respondents were taken as many as 65 peopleusing the census method. Data analysis technique using simple linear regression with dataprocessing using program SPSS 16. Based on R Square value equal to 0,107 or 10,7%. Thisshows that the variables Education and Training (X), contributed to the influence ofProductivity at PT. Jatim Jaya Perkasa of 10.7%, while the rest of 89.3% influenced by othervariables not examined in this study.